Frank Moore Cross and Archaeology - Herr, Larry G. (Bulletin of ASOR, 2014)
This paper studies the contributions of Frank Moore Cross to the field of archaeology in the southern Levant. It looks at his archaeological publications and editorial activities; the interest he maintained in archaeology even as it developed in several different directions; the ways he encouraged other non-archaeologists in various types of archaeological pursuits; and how he encouraged archaeologists toward a holistic practice of the wider disciplines relevant to the region's antiquity.